Lyrics of the Regional Song “Jember Nusantara” as a Symbol of Identity: Analysis of Language Style and Cultural Representation - Moh. Nawalul Fawaid El Haqi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study employs a qualitative research methodology with an interpretive paradigm. It also conducts an in-depth analysis of the stylistics and cultural representations in Linkrafin's song “Jember Nusantara.” The primary data for this study consist of the lyrics of the song. An analytical framework is built on Keraf's (2009) stylistic taxonomy to identify and categorize stylistic devices systematically. This stylistic analysis is then explicitly integrated with Hall's (1997) theoretical concept of cultural representation to interpret the deeper socio-cultural meanings encoded in the text. The findings indicate that the song utilizes a variety of stylistic devices, including metaphor, personification, hyperbole, repetition, and parallelism. This stylistic ensemble is further strengthened by deliberate diction tinged with distinctive local, spiritual, religious, and Javanese-philosophical nuances. The explicit relationship between these stylistic forms and cultural representations is demonstrated through the analysis. Metaphor and personification demonstrate active construction of the symbolic landscape of cultural identity. Hyperbolic expressions and resonant repetition articulate collective aspirations and values. Together, these elements form a complex representational system that reflects societal values ​​related to the revival and celebration of Jember's diverse resource potential. Therefore, the strategic use of figurative language in “Jember Nusantara” serves to shape and project a cohesive regional identity symbolically. Thus, this study concludes that the lyrical composition goes beyond simple description to create a narrative of hope and articulate a cultural vision for Jember Regency. In this regard, it also aims to foster an inclusive revival of Jember Regency by challenging the notion of marginalization through its representative discourse.